Cabira rangarajani n. sp. (Polychaeta: Pilargidae) from the Goa coast, central west coast of India - Mandal, Sumit; Harkantra, Sadanand N.; Salazar-Vallejo, Sergio I. (Zootaxa, 2007)
Cabira rangarajani n. sp., is described from the Goa coast, in central west coast of India. It differs from C. brevicirris (Rangarajan, 1964), by having a single type of neurochaetae while the other species has three types. The new species also differs from the type species, C. incerta Webster, 1879 with regards to the relative length of the fused prostomium and peristomium, size of the palps and antennae and in having relatively smaller anterior appendages. A key to identify all species in the genus is also included.